Does Prior Government Assistance Reduce Food or Housing Assistance among Low‐Income and Food Insecure Households?. Issue 3 (7th September 2017) - Nielsen, Robert B.; Seay, Martin C.; Wilmarth, Melissa J.
Abstract : Despite extensive research into the receipt of government food and housing assistance separately, only limited evidence informs the possibility that the receipt of assistance for one basic need could reduce the need for assistance meeting another basic need. To investigate this possibility among food insecure and low‐income households we examined four years of data from each of the 2004 and 2008 panels of the Survey of Income and Program Participation. Among low‐income and food insecure households we found no evidence that one type of assistance reduced later receipt of the second type of assistance. Rather, results from conditional logistic regression models indicated that receiving one type of assistance was associated with a higher probability of receiving the second type of assistance, or that there was no relationship between the two types of assistance. Factors informing these results are discussed in the context of household help‐seeking and government assistance.